5-hydroxymethylcytosine in DNA repair: A new player or a red herring?. Issue 16 (18th August 2017) - Kantidze, Omar L.; Razin, Sergey V.
ABSTRACT: Active DNA demethylation performed by ten-eleven translocation (TET) enzymes produces 5-hydroxymethylcytosines, 5-formylcytosines, and 5-carboxylcytosines. Recent observations suggest that 5-hydroxymethylcytosine is a stable epigenetic mark rather than merely an intermediate of DNA demethylation. However, the clear functional role of this new epigenetic player is elusive. The contribution of 5-hydroxymethylation to DNA repair is being discussed currently. Recently, Jiang and colleagues have demonstrated that DNA damage response-activated ATR kinase phosphorylates TET3 in mammalian cells and promotes DNA demethylation and 5-hydroxymethylcytosine accumulation. Moreover, TET3 catalytic activity is important for proper DNA repair and cell survival. Here, we discuss recent studies on the potential role of 5-hydroxymethylation in DNA repair and genome integrity maintenance.